Role of Alternative Dispute Resolution as a Mechanism for Administration of Justice - Renu, Shailja Chauhan (International Journal of Science and Research (IJSR), 2019)
Desire for quick and affordable justice is universal. Right to speedy trial is a right to life and personal liberty of every citizen guaranteed under Article 21 of the Constitution, which ensures just, fair and reasonable procedure. Alternative Dispute Resolution mechanisms have become more crucial for businesses operating in India as well as those doing businesses with Indian firms. There are various reasons for which ADR is preferred over the conventional way of resolving the disputes. India being a developing country, going through major economic reforms within the framework of the rule of law, for expeditious resolution of disputes and lessening the burden on the courts, alternative mechanisms for resolution (ADR) are the only alternative through arbitration, conciliation, mediation and negotiation.

eAccess to Justice - Benyekhlef, Karim; Bailey, Jane; Burkell, Jacquelyn; Gélinas, Fabien (Law, Technology and Media, 2016)
Part I of this work focuses on the ways in which digitization projects can affect fundamental justice principles. It examines claims that technology will improve justice system efficiency and offers a model for evaluating e-justice systems that incorporates a broader range of justice system values. The emphasis is on the complicated relationship between privacy and transparency in making court records and decisions available online.Part II examines the implementation of technologies in the justice system and the challenges it comes with, focusing on four different technologies: online court information systems, e-filing, videoconferencing, and tablets for presentation and review of evidence by jurors. The authors share a measuring enthusiasm for technological advances in the courts, emphasizing that these technologies should be implemented with care to ensure the best possible outcome for access to a fair and effective justice system.Finally, Part III adopts the standpoints of sociology, political theory and legal theory to explore the complex web of values, norms, and practices that support our systems of justice, the reasons for their well-established resistance to change, and the avenues and prospects of eAccess. The chapters in this section provide a unique and valuable framework for thinking with the required sophistication about legal change.Published in English.

Fairness in class action settlements - Piché, Catherine (McGill University, 2011)
To be made effective, class action settlements must be negotiated fairly, be perceived as fair and reasonable by the settlement parties such that they agree to their terms and substance, and be characterized as fair, reasonable and adequate by a court at the occasion of a settlement approval hearing. But how is settlement fairness defined, in a collective litigation context? By which process is the evaluation of fairness made and the approval given by the court? What role does the court correspondingly have, in that context? This thesis explores the legal policy and reasoning behind the mandatory judicial approval of class settlements, the process by which it is sought and obtained, the currently relevant factors and indicia of settlement fairness which support all decisions to approve, and the roles of the principal settlement actors, particularly the settlement judge. It suggests hypotheses for reform applicable to these approval processes, roles of the actors and standard of settlement fairness. These hypotheses are tested, for their plausibility, against empirical data obtained from the qualitative interviews of seventeen judges conducted by the author in four target jurisdictions that have similar approaches to class action settlement approvals, and where class action litigation activity is heavy: Quebec, Ontario, British Columbia, and the United States federal courts. Ultimately, the thesis proposes final recommendations for reform of the class action settlement approval procedure.
Keywords: Class action; Class action settlement; Settlement parties